(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines psycholinguistic aspects in the interpretation of social issues presented in Chingiz Aitmatov’s novel “Farewell, Gulsary!”. Through the protagonist Tanabai’s life, the author highlights societal transformations during collectivization and Soviet ideology. The narrative addresses social inequality, individual suppression, and the erosion of traditional values under state policies. Special attention is given to linguistic and psychological aspects that reveal the characters’ inner experiences and their struggle to preserve individuality under stringent social control.